(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Pilonidal sinus over sacrococcygeal area is an acquired condition which affects young male adults usually. We did a retrospective chart review in the department of general surgery ,Kalinga Institute of Medical Sciences ,Bhubaneswar, for patients who underwent limberg flap repair for pilonidal sinus from sept 2015 to sept 2021 (6 years and 8 months) .A total of 49 patients with 40 males and 9 females respectively, were operated and they had a minimal post operative pain ,average post operative hospital stay of 6 days and early return to work in 3 weeks. Four out of 49 patients developed seroma ,out of which 1 was lost to follow up .Remaining 3 took two weeks to heal with regular dressings and no recurrence so far .One patient developed stitch granuloma and was treated conservatively. Hence Limberg flap for sacrococcygeal pilonidal sinus was found to be very useful in terms of post operative pain ,infection rate,patient compliance ,early return to work and almost nil recurrence rates.